The transmembrane receptor TIRC7 identifies a distinct subset of immune cells with prognostic implications in cholangiocarcinoma - Albrecht, Thomas; Goeppert, Benjamin; Brinkmann, Fritz; Charbel, Alphonse; Zhang, Qiangnu; Schreck, Johannes; Wilhelm, Nina; Singer, Stephan; Köhler, Bruno Christian; Springfeld, Christoph; Mehrabi, Arianeb; Schirmacher, Peter; et al. (Cancers, 2021)
Cholangiocarcinoma (CCA) is a heterogeneous malignancy with a dismal prognosis. Therapeutic options are largely limited to surgery and conventional chemotherapy offers limited benefit. As immunotherapy has proven highly effective in various cancer types, we have undertaken a quantitative immunohistopathological assessment of immune cells expressing the immunoinhibitory T cell immune response cDNA 7 receptor (TIRC7), an emerging immunoinhibitory receptor, in a cohort of 135 CCA patients. TIRC7+ immune cells were present in both the tumor epithelia and stroma in the majority of CCA cases with the highest levels found in intrahepatic CCA. While intraepithelial density of TIRC7+ immune cells was decreased compared to matched non-neoplastic bile ducts, stromal quantity was higher in the tumor samples. Tumors exhibiting signet ring cell or adenosquamous morphology were exclusively associated with an intraepithelial TIRC7+ phenotype. Survival analysis showed intraepithelial TIRC7+ immune cell density to be a highly significant favorable prognosticator in intrahepatic but not proximal or distal CCA. Furthermore, intraepithelial TIRC7+ immune cell density correlated with the number of intraepithelial CD8+ immune cells and with the total number of CD4+ immune cells. Our results suggest the presence and prognostic relevance of TIRC7+ immune cells in CCA and warrant further functional studies on its pharmacological modulation.
Gesehen am 13.09.2022